”Queerness is unstoppable” - Kim S. P. Minuva (Kvinder, Køn & Forskning)
During the 2010s, video game content and subsets of the gaming community have been diverging in polarized directions regarding LGBTQ topics in video game culture. On the basis of these discourses, this study utilizes framing and discourse analysis to examine how video game publications frame LGBTQ topics in gaming. Analyzing 269 articles published between 2002 and 2020, it fi nds that 57,2% of articles utilize framing characterized by egalitarian equality, compared to 0,7% that use traditionalist morality framing, while 36,1% use neutral framing. A majority of articles likewise deploy politically loaded keywords in a sincere manner rather than a veiled manner, in which these words function as stand-ins for conservative views. Further, the study points to conservative discourses like Gamer-Gate affecting the output of articles between 2014 and 2015 and charts the potential construction of a journalistic paradigm in which journalists do not utilize slurs. This paradigm and high levels of egalitarian and neutral framing differ from previous findings regarding framing in game journalism.